2003
DOI: 10.1016/s0920-5632(03)01523-8
|View full text |Cite
|
Sign up to set email alerts
|

Electric polarizability of hadrons

Abstract: The electric polarizability of a hadron allows an external electric field to shift the hadron mass. We try to calculate the electric polarizability for several hadrons from their quadratic response to the field at a = 0.17 fm using an improved gauge field and the clover quark action. Results are compared to experiment where available.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 12 publications
4
25
1
Order By: Relevance
“…(11) of [1].) Compilations of experimental results for neutron electric polarizability have been given in [2,3].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…(11) of [1].) Compilations of experimental results for neutron electric polarizability have been given in [2,3].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…Lattice four point function techniques have also been designed to extract neutral or charged particle electric polarizabilities [45] (chiral symmetry can sometimes be used to reduce the calculation to two point functions [46]), but these methods are more difficult to carry out on the lattice. Early results of the present study have been reported in [47]. tables 2…”
Section: Electric Polarizabilitiesmentioning
confidence: 62%
“…To be complete we note that by using background electric fields, electric polarizabilities [31,32] and the electric dipole moment of the nucleon [33] have been investigated. To apply a spatially constant background magnetic field aligned in the z-direction in a lattice simulation, one takes a SU(3) gauge-configuration and modifies the link fields by…”
Section: Lattice Qcd and Background Fieldsmentioning
confidence: 99%